The impact of the international environment on the development of enterprises providing accommodation services in the Lublin voivodeship - Kuźmicki, Marek (Wpływ otoczenia międzynarodowego na rozwój przedsiębiorstw świadczących usługi noclegowe w województwie lubelskim, 2020)
The aim of this article is to present the opinions of owners of year-round accommodation facilities operating in the Lublin voivodeship, concerning the impact of the international environment on the development of enterprises providing accommodation services. The assessment is based on the author’s own research conducted with the use of the CATI method in April and May 2018. Entrepreneurs rarely see opportunities and threats related to the international environment. They seem to think “in a local way”. Generally, the most positive feedback on pro-developmental actions related to the international environment is provided by respondents from urban-rural communes. Membership in international structures, including the European Union, gives a lot of opportunities for development. The entrepreneurs participating in the survey should be even more active while monitoring EU forms of support and applying for EU projects
Biblioteka Regionalisty, 2020, Nr 20, s. 70-78
Keywords: international environment; impact; accommodation company; otoczenie międzynarodowe; wpływ; przedsiębiorstwo noclegowe